A combined non-targeted and targeted metabolomics approach to study the stereoselective metabolism of benalaxyl enantiomers in mouse hepatic microsomes. (May 2016) - Wang, Xinru; Wang, Dezhen; Wang, Yao; Zhang, Ping; Zhou, Zhiqiang; Zhu, Wentao
Abstract: Understanding of xenobiotic metabolism is necessary for risk assessment as well as toxicological research. In the present study, nanoLC/LTQ-Orbitrap mass based non-targeted metabolomics method coupled with ultra-performance liquid chromatography (UPLC)/triple quadrupole mass based targeted metabolomics method was carried out to investigate the stereoselective metabolism of benalaxyl in mouse hepatic microsomes. As a result, 7 metabolites of benalaxyl were identified, including 5 previously reported and 2 newly identified metabolites in present work. Hydroxylation, oxidation and esterolysis were major biotransformation reactions of benalaxyl in mouse hepatic microsomes. For stereoselective metabolism study, (−)-R-benalaxyl degraded much faster than its antipode with the t1/2 of 81.24 and 190.38 min for (−)-R- and (+)-S-benalaxyl, respectively. More importantly, stereoselectivity was also observed in the formation of the identified metabolites. In conclusion, the combined use of the mass spectrometry based targeted and non-targeted metabolomics provided a new approach to investigate stereoselective metabolism and identify novel metabolites of chiral pesticides. This study highlights the stereoselective metabolic profile of benalaxyl enantiomers and provides reliable data for benalaxyl toxicological risk assessment in mammal. Graphical abstract: Highlights: A combined non-targeted and targeted metabolomics strategy was established. Seven metabolites of benalaxyl were identified, including two novel metabolites. Metabolic profile of benalaxyl in mouse hepatic microsomes was illustrated. Metabolism of benalaxyl enantiomers in mouse hepatic microsomes was stereoselective. Abstract : Seven metabolites of benalaxyl were identified, including two newly identified metabolites. Metabolism of benalaxyl enantiomers was stereoselective.